2015
DOI: 10.4103/0970-2113.156216
|View full text |Cite
|
Sign up to set email alerts
|

Vascular air embolism after contrast administration on 64 row multiple detector computed tomography: A prospective analysis

Abstract: Background:Vascular air embolism is being progressively reported as a nonfatal event with increase in use of computed tomography (CT) as a diagnostic modality. This study was undertaken to study the frequency and site of vascular air embolism in patients undergoing contrast-enhanced CT (CECT) and analyze CT parameters that influence its prevalence and final outcome.Materials and Methods:This was a prospective study approved by departmental ethics committee. Presence and location of air emboli in 200 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 14 publications
0
34
1
Order By: Relevance
“…In clinical scenarios involving contrast enhanced studies with power injectors, the risk for retrograde cerebral venous air embolism is likely increased [6]. A prospective study from India examined the risks of air embolism in 200 patients that underwent contrast enhanced CT and found that iatrogenic air embolism occurred in 7% of all studies [7].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical scenarios involving contrast enhanced studies with power injectors, the risk for retrograde cerebral venous air embolism is likely increased [6]. A prospective study from India examined the risks of air embolism in 200 patients that underwent contrast enhanced CT and found that iatrogenic air embolism occurred in 7% of all studies [7].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on non-fatal iatrogenic air embolism following a CECT examination are limited. Most iatrogenic air emboli were reported as being small in size (defined as less than 1 cm) 2–4. Compared with large air embolism, such small air embolism is usually asymptomatic and non-fatal.…”
Section: Discussionmentioning
confidence: 99%
“…The most common location of VAE is the main pulmonary artery (5.52%), followed by right atrial appendage (2.2%), left brachiocephalic vein (1.65%) and superior vena cava (0.55%),2 4 4 as air bubbles tend to rise within the most non-dependent areas in a vessel or cardiac chamber contributed by the buoyancy of air in a fluid medium. Although rapid injection of air amounting to 100–200 mL has been shown to raise the mortality risk following cardiopulmonary arrest,2 another study showed no association between the presence of air emboli and the volume of contrast, flow rate, site and the size of intravenous access 4. However, the duration of persistence of air embolism at different vasculature is unclear as there is no literature available about the topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of central vascular air embolism has demonstrated no relationship to technical factors such as contrast flow rate, site and size of peripheral cannula, neither in the study by Groell et al nor in a more recent, similar study of 200 patients. 2 …”
Section: Discussionmentioning
confidence: 99%